10.6k views
2 votes
Rewrite the quadratic equation in the form y = a(x − h)2 + k. y = 4x2 − 16x + 64

User Avdgaag
by
5.4k points

2 Answers

4 votes

Answer:

y=4(x-2)^2 +48

Explanation:

User Edmund Gentle
by
5.0k points
5 votes

Answer:

y = 4(x-2)^2 +48

Explanation:

y = 4x^2 − 16x + 64

Factor out a 4

y = 4(x^2 − 4x ) +64

Now we need to complete the square (-4/2) ^2 = 4

But remember the 4 on the outside. We add 4 on the inside of the parentheses, but are really adding 4*4 = 16 If we add 16 we need to subtract 16 to remain equal

y = 4(x^2 -4x +4) -16+64

= 4 (x^2 -4x+4) +48

Factor the parentheses

= 4(x+ (-4/2) ) ^2 +48

y = 4(x-2)^2 +48

h = 2, k=48


User Smelch
by
5.5k points